2018
DOI: 10.1049/mnl.2018.5097
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer‐mediated synthesis and characterisation of platinum nanocomposite and its anti‐fungal activity against A. parasiticus and A. flavus

Abstract: The green synthesis of the platinum (Pt) nanocomposite was achieved using a natural biopolymer gum kondagogu (GK), a widely preferred reducing agent because of its biocompatible and biodegradable nature. The synthesised GK Pt nanoparticle (GKPtNP) were characterised by using different analytical techniques such as ultraviolet-visible spectrophotometer, transmission electron microscope, X-ray diffraction, and inductively coupled plasma mass spectroscopy (ICP-MS). The objective of the present work was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The present results are in agreement with Vinod et al , [21] and Godugu and Sashidhar [22] who reported GKPt NPs to be 2.4 ± 0.7 nm and 2–4 ± 0.50 nm, respectively. Sreedhar et al [72] reported 2–3 nm with gum acacia stabilised Pt NPs while Kora and Rastogi [73] reported 4.4 ± 0.5 nm with gum olibanum stabilised Pt NPs.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The present results are in agreement with Vinod et al , [21] and Godugu and Sashidhar [22] who reported GKPt NPs to be 2.4 ± 0.7 nm and 2–4 ± 0.50 nm, respectively. Sreedhar et al [72] reported 2–3 nm with gum acacia stabilised Pt NPs while Kora and Rastogi [73] reported 4.4 ± 0.5 nm with gum olibanum stabilised Pt NPs.…”
Section: Resultssupporting
confidence: 93%
“…The percent conversion of Pt ions to NPs was 85.11% suggesting the excellent reductive property of GK in the formation of GKCPt NC. Earlier, Godugu and Sashidhar [22] reported percent conversion of Pt ions to NPs at 56.06% in GKPt NP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations